The Effect of Snakes and Ladders Learning Media on Mathematics Learning Outcomes at SD Plus Fatimah Az-Zahro - Masrifatul Mahmudah (Madrosatuna: Journal of Islamic Elementary School, 2018)
The aim of this research was to know whether or not influenced and how much the influenced learning model snake ladder in increasing of studying resulted of Mathematics for first grade students in SD plus Fatimah Az-Zahro’. This study was used a quantitative experimental with pre – Experimental observation. The population that made as an observation object was in the first grade in SD plus Fatimah Az- Zahro’. The data collection techniques used test that consist of two tests (pre-test and post-test). The observation result showed was the influenced between learning model of snack ladder with study resulted. Got of 0,00 < 0,05 value of signification level 5% getting smaller than the wrong level so it can took a concluded that the influenced of learning media of snack ladder to the studying result, had proven of data counting resulted with used Eta Squared ways got 0,48 < 0,14 value that meant had a big influenced.